(untitled) (Research, Society and Development, 2020)
This article aims to expose the teaching practice performed in the field of inclusive education, focusing on the development of communication, affection, interaction, self-esteem and enhancement of natural skills, with emphasis on artistic design, the student with intellectual disabilities and autism. We opted for the case study, with participant observation, since the student is the target audience of Specialized Educational Care. The work has been refined and developed, having as its main locus the Multifunctional Resource Room of an elementary school in the city of Maranguape, Ceará, Brazil, especially in the first semester of 2014. It focuses on the student’s educational process, the from the relationship between the family, the school and the society in which it is inserted, seeking to know their needs, as well as their natural abilities. The contribution of legal devices such as PCN’s (1997) and also the theoretical foundation of human behavior scholars and their development were necessary, namely: Piaget (1997), under the constructivist view; Gardner (2001) with the theory of Multiple Intelligences; besides the contribution of Figueiredo (2010). As a result, starting from the inclusion process with the student’s permanence in the Specialized Educational Care and regular school, there was an evolution in the learning and development of his active, autonomous, creative and participative posture. The conclusions point to an effective teaching practice through artistic design involving on the one hand the student with disabilities and on the other the teaching professionals of the Specialized Educational Care.